2018
DOI: 10.1007/s00253-018-9525-0
|View full text |Cite
|
Sign up to set email alerts
|

International Space Station conditions alter genomics, proteomics, and metabolomics in Aspergillus nidulans

Abstract: The first global genomic, proteomic, and secondary metabolomic characterization of the filamentous fungus Aspergillus nidulans following growth onboard the International Space Station (ISS) is reported. The investigation included the A. nidulans wild-type and three mutant strains, two of which were genetically engineered to enhance secondary metabolite production. Whole genome sequencing revealed that ISS conditions altered the A. nidulans genome in specific regions. In strain CW12001, which features overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 80 publications
4
21
0
Order By: Relevance
“…The ability to perform high-throughput sample processing onboard the ISS followed by NGS makes it possible for astronauts to know what microbes and their properties are in the environment, at any given time. This is significant when you consider that omics analyses on ISS samples (performed on Earth) have detected novel organisms and/or those with unique properties (Checinska Sielaff et al, 2017;Romsdahl et al, 2018Romsdahl et al, , 2019Singh et al, 2019;Urbaniak et al, 2019). Furthermore, many terrestrial species that have been sent from Earth to grow on the ISS have become more virulent and antibiotic resistant, and have formed more biofilms (Yamaguchi et al, 2014), all of which are properties that can affect the health of astronauts and the stability of the spacecraft.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to perform high-throughput sample processing onboard the ISS followed by NGS makes it possible for astronauts to know what microbes and their properties are in the environment, at any given time. This is significant when you consider that omics analyses on ISS samples (performed on Earth) have detected novel organisms and/or those with unique properties (Checinska Sielaff et al, 2017;Romsdahl et al, 2018Romsdahl et al, , 2019Singh et al, 2019;Urbaniak et al, 2019). Furthermore, many terrestrial species that have been sent from Earth to grow on the ISS have become more virulent and antibiotic resistant, and have formed more biofilms (Yamaguchi et al, 2014), all of which are properties that can affect the health of astronauts and the stability of the spacecraft.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exposure to radiation needs to be considered particularly when thinking of long-duration missions into deep space (out of Earth's magnetic field), as it is the case for a mission to Mars. This is because radiation-induced mutations can lead to functional changes, particularly in microbial species on board, due to their short generation lifetime (Romsdahl et al 2018a;Meyer et al 2007). For instance, a study aboard Mir showed that a bacterial gene (repsL) cloned in the yeast S. cerevisiae had a mutation rate 2-3 times higher in spaceflight than on ground (Fududa et al 2000).…”
Section: Fungi In the Space Environmentmentioning
confidence: 99%
“…Moreover, characterization of A. nidulans grown on board the ISS was recently reported. Whole genome sequencing revealed that ISS conditions altered the A. nidulans genome in specific regions, and differential expression of genes involved in stress response, carbohydrate metabolic processes and secondary metabolite biosynthesis was observed (Romsdahl et al 2018a). Moreover, a study growing Penicillium rubens in low-shear modelled microgravity showed increased expression of the gene coding for the acyl-coenzyme A: isopenicillin N acyltransferase-an enzyme involved in penicillin biosynthesis (Sathishkumar et al 2015(Sathishkumar et al , 2016.…”
Section: Fungi In the Space Environmentmentioning
confidence: 99%
“…Spaceflight-associated and simulated Mars-like stressors such as radiation, changed gravity and atmosphere, and temperature fluctuations can be challenging for the survival of microorganisms, and a complex mixture of these extraterrestrial factors promotes global genomic, proteomic, and secondary metabolomic changes that result in impaired cellular processes and functions, affecting cell growth, cell morphology and development, virulence and resistance, and biofilm formation (Huang et al, 2018;Zea et al, 2018;de Vera et al, 2019;Romsdahl et al, 2019). Microorganisms evolve different response and adaptation mechanisms to extreme environments; however, many of them are still unknown.…”
Section: Introductionmentioning
confidence: 99%